White Matter Characteristics of Cognitive Impairment in Tap-Test Positive Idiopathic Normal Pressure Hydrocephalus: A Diffusion Tensor Tract-Based Spatial Study - Tang, Yufeng; Yuan, Xiaoqin; Duan, Jinfeng; Zhang, Xianwen; Chen, Jiao; Zhou, Ying; Song, Fangzhou; Zhou, Dong (Frontiers in Neuroscience, 2021)
The present study was designed to systemically evaluate changes in the diffusion tensor imaging (DTI)-derived parameters of iNPH (Idiopathic normal pressure hydrocephalus) patients with different responses to the Tap test (TT), and to correlate cognitive impairment with white matter (WM) degeneration. This study included 22 iNPH patients and 14 healthy controls with structural magnetic resonance imaging (MRI) and DTI scaning. DTI was used to explore the differences in fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) for all participants. DTI parameters were evaluated using an ROI(region of interest)-based and tract-based spatial statistics approach. Neuropsychological assessments and the idiopathic normal pressure hydrocephalus grading scoring scale (iNPHGS)were performed. Compared to the TT non-responders, the TT responders group had significantly lower FA values in the corpus callosum, cingulum cingulate gyrus, superior longitudinal fasciculus, and lower AD values in the right cingulum cingulate gyrus and the left posterior thalamic radiation. Besides, the MD values were significantly increased in the corpus callosum, left anterior corona radiata, and the RD values in the corpus callosum and cingulum cingulate gyrus. In addition, the cognitive improvement was negatively correlated with FA of the corpus callosum, cingulum cingulate gyrus, and MD values of the genu of corpus callosum. While, the cognitive improvement was positively related to the AD of the cingulum cingulate gyrus, superior longitudinal, and RD values of the corpus callosum, cingulum cingulate gyrus and uncinate fasciculus. The ROI specific WM lesions in iNPH patients are the underlying basis for cognitive impairment.